EUDR and Potential Collaboration with Malaysian Palm Oil Industry Stakeholders - Muthu, Uthaya Kumar (2023)
The European Union Deforestation Regulation (EUDR) is aimed at promoting sustainable supply chains and ensuring that products imported into the EU are not by any chance associated with deforestation, human rights abuses, or environmental degradation. It entered into force on June 29, 2023, with large companies having till December 2024 and small and medium-sized (SMEs) companies in June 2025. This paper aims to focus on the challenges faced by specifically SMEs and smallholders in the palm oil industry. The sector employs nearly 450,000 smallholders with challenges varying from limited resources to capacity constraints in meeting EUDR criteria. The paper will also look into the policy framework and implementation mechanisms of the EUDR, including the due diligence requirements, certification schemes, and traceability systems. With the recent high level of engagement under the Council of Palm Oil Producing Countries (CPOPC) and the EU’s openness for further engagement the paper aims to explore the potential collaboration between the bloc and the Malaysian palm oil industry to support smallholders. It could be anything between technology sharing, capacity building, or financial support to facilitate the adoption of sustainable practices by smallholders. As a reference point, this paper would also analyze the multi-stakeholder dialogue that the EU established for a sustainable cocoa production. As non-compliance could result in a fine of at least 4%, seizing of revenue made, or temporary exclusion from public procurement processes, the research findings aim to provide valuable insights for multiple stakeholders and ensure smallholders' position in the supply chain remains intact.